Preparation method of 3D-printable high-toughness interpenetrating network hydrogel elastomer

By preparing high-toughness interpenetrating network hydrogel elastomer, the problems of low mechanical strength and poor toughness of traditional hydrogels are solved, and the effects of high mechanical properties and excellent biocompatibility are achieved.

CN119684638AActive Publication Date: 2025-03-25GUANGXI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411849995.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Traditional hydrogels have low mechanical strength and poor toughness, which limit their application in areas where high mechanical properties are required.

Method used

By preparing a high-toughness interpenetrating network hydrogel elastomer, a high-toughness interpenetrating network structure is formed by using raw materials such as polyvinyl alcohol, methacrylic anhydride, hydroxypropyl cellulose, chitosan quaternary ammonium salt, carboxylated cellulose nanofibers and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenyl acetone through photocuring and immersing sodium citrate solution.

Benefits of technology

It realizes the high mechanical strength and toughness of hydrogel elastomers, can withstand high compression and tensile stresses, and quickly restores to its original state after external forces, and has excellent biocompatibility and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684638A_ABST
    Figure CN119684638A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a 3D-printable high-toughness interpenetrating network hydrogel elastomer and a preparation method and application thereof, and aims to solve the problems that traditional hydrogel is poor in mechanical property, prone to embrittlement and the like. The hydrogel is mainly composed of methacrylic acid polyvinyl alcohol (PVA-MA), hydroxy propyl cellulose (HPC), chitosan quaternary ammonium salt (HACC) and carboxylated cellulose nanofiber (CNF), a hydrogel elastomer is formed after illumination under specific ultraviolet light, and then salt solution post-treatment is carried out. PVA-MA and HPC are connected through a hydrogen bond, CNF and HACC generate electrostatic attraction, and meanwhile, CNF and HACC form a hydrogen bond with carboxyl of HPC, so that an interpenetrating network is formed. After the formed hydrogel is soaked in a salt solution, strong hydrophobic interaction and chain constraint are introduced through a Hough Muss ion effect, so that the hydrogel is endowed with excellent toughness, the hydrogel can bear 911.11 + / -13.85 kPa external force (compressed to 30% of the original height), the elongation at break can reach 100% or above, and the breaking strength can reach 2000 kPa or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a 3D printable high-toughness interpenetrating network hydrogel elastomer hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel is a polymer material with a three-dimensional network structure that can absorb a large amount of water while maintaining its shape and structure. Due to its good biocompatibility, adjustable physical and chemical properties, and softness similar to biological tissues, hydrogel has broad application prospects in biomedicine, tissue engineering, drug delivery, sensors and other fields. However, traditional hydrogels usually have problems of low mechanical strength and poor toughness, which limits their application in some fields that require high mechanical properties. Summary of the invention

[0003] 1. In order to solve the problems of low mechanical strength and poor toughness of existing hydrogels, the present invention provides a 3D printable high-toughness interpenetrating network hydrogel elastomer and its preparation method and application.

[0004] 2. The 3D printable high-toughness interpenetrating network hydrogel elastomer is composed of the following raw materials in parts by weight:

[0005] Polyvinyl alcohol: 0.5-5 parts;

[0006] Methacrylic anhydride: 0.5-5 parts;

[0007] Hydroxypropyl cellulose: 0.5-5 parts;

[0008] Chitosan quaternary ammonium salt: 0.05-0.25 parts;

[0009] Carboxylated cellulose nanofibers: 0.05-0.25 parts;

[0010] 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone: 0.01-1 part;

[0011] Sodium citrate: 5-60 parts;

[0012] Sodium chloride: 5-30 parts;

[0013] Deionized water: 20-100 parts.

[0014] 3. The preparation method of the 3D printable high-toughness interpenetrating network hydrogel elastomer comprises the following steps:

[0015] (1) heating polyvinyl alcohol in a water bath at 90° C. to 95° C., dissolving it in 20 to 150 ml of deionized water to obtain a polyvinyl alcohol solution with a mass fraction of 1.5% to 10%, adding methacrylic anhydride with a concentration of 1:1 with polyvinyl alcohol to obtain a mixed solution A, and obtaining a PVA-MA hydrogel by photocuring, which is recorded as PM hydrogel;

[0016] (2) Adding hydroxypropyl cellulose (equivalent to 20% to 200% of polyvinyl alcohol) to the mixed solution A, heating and stirring in a water bath for 12 to 48 hours, and obtaining a mixed solution B after full dissolution, and obtaining a PVA-MA / HPC hydrogel by photocuring, which is recorded as PMH hydrogel;

[0017] (3) chitosan quaternary ammonium salt and carboxylated cellulose nanofibers were added to the mixed solution B in a ratio of 1:1, and the mixed solution C was obtained after stirring. PVA-MA / HPC / HACC / CNF hydrogel was obtained by photocuring, which was recorded as PMHC hydrogel;

[0018] (4) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the mixed solution C, stirring thoroughly to obtain a mixed solution D, and photocuring to obtain a PVA-MA / HPC / HACC / CNF / I2959 hydrogel, which is denoted as PMHI hydrogel;

[0019] (5) After the PMHI hydrogel is immersed in sodium citrate solutions of different concentrations, it is immersed in sodium chloride solutions of different concentrations again. After a certain period of time, a high-toughness interpenetrating network hydrogel elastomer is obtained.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) Compared with other hydrogels, the hydrogel elastomer of the present invention has good mechanical strength and can withstand an external force of 911.11±13.85 kPa (compressed to 30% of the original height). It can maintain structural integrity and is not easy to break when subjected to strong external force impact. This strong mechanical stability provides a solid foundation for its application in various complex environments with high strength requirements.

[0022] (2) Good toughness: The hydrogel elastomer has good toughness. While having good compressive stress, it can withstand a tensile stress of 2251.06±12.35 kPa. When deformed by external stretching, it can quickly return to its original shape after the external force is removed due to its excellent elastic properties, and is not prone to permanent damage.

[0023] (3) The hydrogel elastomer of the present invention has excellent biocompatibility, has no toxic side effects on organisms, can maintain high biological safety and stability, and can be used in the biomedical field.

[0024] (4) The preparation method of the hydrogel elastomer of the present invention is simple and easy to implement, does not require the aid of high-end complex instruments and equipment and cumbersome operation steps, is low-cost, and is easy for industrial production.

[0025] (5) The hydrogel of the present invention is environmentally friendly and can be reused multiple times without significantly reducing performance due to repeated use, thereby effectively reducing waste generation and lowering resource loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following is a brief introduction to the drawings required for describing the embodiment. Among them:

[0027] Figure 1 The comparison diagram and the physical diagram of the PVA grafting MA reaction before and after the present invention;

[0028] Figure 2 Schematic diagram of mechanical properties and rebound change curve of PM hydrogel under different stresses and strains of the present invention;

[0029] Figure 3 Schematic diagram of mechanical properties and rebound change curve of PMH hydrogel under different stresses and strains of the present invention;

[0030] Figure 4 Schematic diagram of mechanical properties and rebound change curve of PMHC hydrogel under different stresses and strains of the present invention;

[0031] Figure 5 It is a schematic diagram of the mechanical properties and the rebound change curve of the PMHI hydrogel of the present invention under different stresses and strains after being immersed in different sodium citrate solution concentrations;

[0032] Figure 6 This is a comparison diagram of the PMHI hydrogel of the present invention after being immersed in different concentrations for 24 hours.

[0033] Figure 7 This is a comparison diagram of the PMHI hydrogel of the present invention before and after being immersed in a sodium citrate solution. DETAILED DESCRIPTION

[0034] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0037] The material prepared in the embodiment of the present invention was tested for performance as follows:

[0038] The hydrogel was subjected to compression test using a texture analyzer (TMS-PRO), and the hydrogel was subjected to tensile test using a universal materials testing machine.

[0039] Example 1

[0040] Take 8.0% of the mass of deionized water PVA and add it to 25mL deionized water, heat it in a 95℃ water bath to dissolve it, and add MA (m PVA :V MA =1:1), stir magnetically under light-proof and 500rmp conditions, after the reaction is completed, add HPC with a mass of 100% of PVA mass, add HACC and CNF in a mass ratio of 1:1 to take a total mass of 1.6% of deionized water mass, add I2959 with a mass of 0.02% of PVA mass, heat and stir in a 35°C water bath until the solution is uniform, use a 1ml syringe to extrude the solution into a polytetrafluoroethylene mold, and irradiate with 365nm ultraviolet light for 5min to obtain PMHI hydrogel. Subsequently, soak in 1.4mol / L sodium citrate solution for 24h to obtain a high-toughness interpenetrating network hydrogel elastomer.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the addition amount of HPC, CNF, HACC and I2959 is adjusted to 0%, and the rest of the preparation process is the same as that of embodiment 1 to obtain a hydrogel.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that the addition amount of CNF, HACC and I2959 is adjusted to 0%, and the rest of the preparation process is the same as that of embodiment 1 to prepare the hydrogel.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that the addition amount of I2959 is adjusted to 0%, and the rest of the preparation process is the same as that of embodiment 1 to prepare the hydrogel.

[0047] Example 5

[0048] The difference between this embodiment and embodiment 1 is that the obtained hydrogel is directly tested without post-treatment.

[0049] The tensile and compressive performance tests were performed on the material obtained in the above embodiment, and the compressive strain was set to 70%. The comparison results with embodiment 1 are shown in Table 1.

[0050] Table 1 Comparison of stress and strain in the examples

[0051]

[0052]

[0053] As can be seen from Table 1 above, after adding HPC, the compressive stress and tensile stress of the hydrogel are greatly increased, which has a significant impact on the hydrogel. This is because after adding HPC, the hydroxyl groups on the surface of HPC form hydrogen bonds with the anhydride groups on the surface of PVA-MA, resulting in physical entanglement, increasing the cross-linking sites inside the hydrogel, making the network structure more compact and stable, thereby improving the tensile strength, compressive strength and elastic modulus, so that it can withstand external forces and rebound quickly. When carboxylated CNF and HACC are added to the system, the carboxyl groups on the surface of carboxylated CNF will produce electrostatic attraction with the positively charged HACC, and can also form hydrogen bonds with the carboxyl groups of HPC, thereby forming an interpenetrating network, increasing the number of molecular chain nodes, and the macroscopic manifestation is that the toughness is further enhanced. After adding I2959, the photoinitiator can induce C=C cross-linking at the end of the PVA-MA molecular chain, so that the cross-linking points are sufficient, which can enable the material to initiate polymerization in a short time, improve the bonding force between the internal structures of the hydrogel, and thus the compressive stress and tensile stress are greatly increased. After the formed hydrogel is immersed in a sodium citrate solution, strong hydrophobic interactions and chain constraints are introduced through the Hofmeyrs ion effect, giving the hydrogel excellent strength and toughness.

[0054] Example 6

[0055] The difference between this embodiment and embodiment 1 is that the amount of PVA added is adjusted to 2%, 4%, 6%, and 10% of the mass of deionized water, the amount of HPC, CNF, HACC, and I2959 added is 0%, and no solution is immersed. The rest of the preparation process is the same as that of embodiment 1 to obtain a hydrogel.

[0056] The tensile and compressive performance tests were performed on the material obtained in the above embodiment, and the compressive strain was set to 70%. The comparison results with embodiment 2 are shown in Table 2.

[0057] Table 2 Comparison of stress and strain in the examples

[0058]

[0059]

[0060] Figure 1This is a comparison diagram of the PM hydrogel prepared in Example 6 of the present invention before and after the reaction. It can be seen that before the reaction, methacrylic anhydride appears in the form of oil droplets in the PVA solution, is milky white during the reaction, and becomes a transparent clear solution after the reaction.

[0061] Figure 2 Schematic diagram of the mechanical properties of PM hydrogel prepared in Example 6 of the present invention under different strains and stresses, Figure 2 (a) is the stress-strain diagram obtained from the compression test. It can be seen that with the increase of PVA content, the tensile stress gradually increases, especially when the PVA content is 6% to 8%, there is a significant increase, and the tensile stress of 8% and 10% is not much different. Figure 2 (b) is the stress-strain diagram obtained from the tensile test. When the PVA content is 2%, the sample is too soft and breaks before the tensile test, so it is directly excluded. From the stress-strain diagrams of the other four samples, it can be seen that with the increase of PVA content, the tensile stress gradually increases, and the tensile elongation shows a trend of first increasing and then decreasing. The tensile stress increases suddenly from 6% to 8%, and the tensile elongation decreases from 8% to 10%. Figure 2 (c) is the rebound rate of PM hydrogel. It can be seen that with the increase of PVA content, the rebound elasticity also increases significantly. This is because PVA is the main skeleton structure of the hydrogel network. When its addition amount increases, the hydrogen bonds and C=C photoinduced cross-linking points inside the hydrogel increase, which increases the intermolecular force and improves the mechanical properties.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 1 is that the amount of HPC added is adjusted to 40%, 60%, 80%, and 120% of the mass of PVA, the amount of CNF, HACC, and I2959 added is 0%, and no solution is immersed. The rest of the preparation process is the same as that of embodiment 1 to obtain a hydrogel elastomer.

[0064] The tensile and compressive performance tests were performed on the material obtained in the above embodiment, and the compressive strain was set to 70%. The comparison results with embodiment 3 are shown in Table 3.

[0065] Table 3 Comparison of stress and strain in the examples

[0066]

[0067] Figure 3 This is a schematic diagram of the mechanical properties of the PMH hydrogel prepared in Example 7 of the present invention under different strains and stresses. It can be seen that after the addition of HPC, the mechanical properties of the hydrogel elastomer are greatly improved, but the resilience is reduced compared to before. This may be because the addition of HPC increases the number of molecular chain nodes of the hydrogel elastomer and makes the network connections more dense. Figure 3(a)(b) are stress-strain diagrams obtained from compression tests and stretching. It can be seen that as the amount of HPC added increases, both the compressive stress and the tensile stress gradually increase, but the tensile strain elongation decreases. This may be due to excessive addition of HPC, which results in incomplete dissolution and exists in powder form, so the compressive stress is large. In addition, HPC exists in the form of powder in the hydrogel elastomer. When a tensile test is performed, it will cause plastic deformation of the material, resulting in a small reduction in tensile strain. When the amount of HPC added is too small, the distance between the molecular chains is large. When subjected to external force, the molecular chains are more likely to move. The macroscopic manifestation is that the compressive stress and tensile stress are small, and the deformation amount is large. Figure 3 (c) is the rebound rate of PMH hydrogel. It can be seen that as the amount of HPC increases, the rebound rate gradually increases. However, when the amount of HPC is excessive, the rebound elasticity deteriorates and there is an over-viscosity phenomenon during the preparation process.

[0068] Example 8

[0069] The difference between this embodiment and embodiment 1 is that the total addition amount of CNF and HACC is adjusted to 0.4%, 0.8%, 1.2%, and 2.0% of the mass of deionized water, the addition amount of I2959 is 0%, and no solution is immersed. The rest of the preparation process is the same as that of embodiment 1 to obtain hydrogel.

[0070] The tensile and compressive performance tests were performed on the material obtained in the above embodiment, and the compressive strain was set to 70%. The comparison results with embodiment 4 are shown in Table 4.

[0071] Table 4 Comparison of stress and strain in the examples

[0072]

[0073] Figure 4 This is a schematic diagram of the mechanical properties of the PMHC hydrogel prepared in Example 8 of the present invention under different strains and stresses. It can be seen that after adding CNF and HACC, the compressive stress and tensile stress are both improved compared with the PMH hydrogel elastomer. Figure 4 (a) is the stress-strain diagram obtained from the compression test. It can be seen that when the compressive stress is between 0 and 50 kPa, the deformation curve of the material is close to linear. When it is between 50 and 200 kPa, the deformation of the material is similar to the characteristics of a tangent curve. When the stress increases to 200 to 400 kPa, the material reaches its yield limit, and the rate of change of the deformation of the material decreases rapidly. At this time, the curve shows a large upward trend. Figure 4 (b) is the stress-strain diagram obtained from the tensile test. It can be seen that the tensile strain of the hydrogel elastomer is mostly around 200%. Compared with PMH, the tensile performance is greatly improved. However, when the addition amount is too large, some of the molecular chains in the hydrogel elastomer are dense and tightly cross-linked, thereby reducing the tensile strain. Figure 4 (c) is the rebound rate of PMHC hydrogel elastomer. It can be found that the rebound rate of all samples has increased. When the total addition amount of CNF and HACC is 1.6%, the sample rebound rate is the highest. This may be because the addition of CNF and HACC breaks the original structure of HPC, forming an interpenetrating double network structure, increasing the restriction on the movement of the molecular chain, resulting in a greater force required for the relative position between molecules. At the same time, there is a hydrogen bond between the rich hydroxyl groups of CNF and PVA-MA and HPC. The carboxyl groups on the molecular chain will undergo ionic crosslinking with the quaternary ammonium ions on HACC, forming an interpenetrating network with HPC, thereby improving the mechanical properties of the hydrogel.

[0074] Example 9

[0075] The difference between this embodiment and embodiment 1 is that the concentration of sodium citrate is adjusted to 0.2 mol / L, 0.6 mol / L, 1 mol / L, and 1.8 mol / L, and the rest of the preparation process is the same as that of embodiment 1 to obtain a hydrogel.

[0076] The tensile and compressive performance tests were performed on the material obtained in the above embodiment, and the compressive strain was set to 70%. The comparison results with embodiment 5 are shown in Table 5.

[0077] Table 5 Comparison of stress and strain in examples

[0078]

[0079] Figure 5 This is a schematic diagram of the mechanical properties of the PMHI hydrogel prepared in Example 9 of the present invention under different strains and stresses. It can be seen that the mechanical properties of the hydrogel elastomer soaked in sodium citrate are greatly improved. Figure 5 (a) is the stress-strain diagram obtained from the compression test. It can be seen that with the increase of the concentration of sodium citrate solution, the mechanical properties of the hydrogel elastomer gradually increase, and the mechanical properties suddenly increase from 1.4 mol / L to 1.8 mol / L. This may be because the citrate in the sodium citrate solution forms an electrostatic interaction with the quaternary ammonium root of HACC, and the salting-out effect enhances the copper ion effect, promotes internal cross-linking, and reduces the electrostatic repulsion between molecular segments. Figure 5 (a) is the stress-strain diagram obtained from the compression test. It can be observed that when the sodium citrate solution increases from 0.2mol / L to 1.8mol / L, the tensile strength increases from 247.54±7.6kPa to 4349.20±1.10kPa, but the elongation at break decreases. This may be because HPC is not completely dissolved and exists in the system in powder form, affecting the tensile elongation. However, immersion in a high concentration of sodium citrate solution will increase the crosslinking density, thereby improving the mechanical properties.

[0080] Figure 6The physical picture of the PMHI hydrogel elastomer prepared in Example 9 of the present invention after being immersed in different concentrations for 24 hours shows that the hydrogel elastomer expands at a lower concentration and shrinks at a higher concentration. This may be because at low concentrations, the sodium citrate solution has a lower ionic pressure, resulting in osmotic pressure inside and outside the hydrogel, prompting water molecules to enter the hydrogel, thereby causing expansion; at higher concentrations, the high-concentration sodium citrate solution has a larger ionic strength, causing a salting-out effect, causing the molecular chains in the hydrogel elastomer to aggregate, and water molecules are excluded. At the same time, the high concentration of ions weakens the electrostatic repulsion between the chains, resulting in more intensive hydrogen bonds and hydrophobic effects, which manifests as hydrogel shrinkage.

[0081] Figure 7 This is a comparison diagram of the PMHI hydrogel elastomer prepared in Example 9 of the present invention before and after being immersed in a sodium citrate solution. It can be found that the hydrogel is opaque milky white before immersion, and after immersion, the hydrogel is translucent around and opaque milky white in the middle.

[0082] In summary, the present invention obtains a high-toughness interpenetrating network hydrogel elastomer hydrogel, PVA grafted with MA to obtain unsaturated carbon-carbon double bonds, and after being excited by 365nm ultraviolet light, I2959 absorbs light energy to generate free radicals with high reactivity, thereby initiating the polymerization of PVA-MA monomers. In addition, there is a reversible hydrogen bond between the hydroxyl groups of PVA-MA and HPC, thereby forming the first layer of network. The carboxyl group (-COO - ) and the quaternary ammonium radical (NH4 + ) produce hydrogen bond interactions. HPC molecules will autonomously arrange into a regular cholesteric structure under the action of certain water molecules. The addition of CNF and HACC breaks the original regular layered structure and forms an interpenetrating network. The gel elastomer is immersed in a sodium citrate solution. The citrate radical and the NH4 + The hydrogen bonding between the hydrogel networks is further strengthened through the salting-out effect.

[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer, characterized in that: (1) heating polyvinyl alcohol in a water bath at 90° C. to 95° C., dissolving it in 20 to 150 ml of deionized water to obtain a polyvinyl alcohol solution with a mass fraction of 1.5% to 10%, adding methacrylic anhydride with a concentration of 1:1 with polyvinyl alcohol to obtain a mixed solution A, and obtaining a PVA-MA hydrogel by photocuring, which is recorded as PM hydrogel; (2) Adding hydroxypropyl cellulose (equivalent to 20% to 200% of polyvinyl alcohol) to the mixed solution A, heating and stirring in a water bath for 12 to 48 hours, and obtaining a mixed solution B after full dissolution, and obtaining a PVA-MA / HPC hydrogel by photocuring, which is recorded as PMH hydrogel; (3) chitosan quaternary ammonium salt and carboxylated cellulose nanofibers were added to the mixed solution B in a mass ratio of 1:1, and the mixed solution C was obtained after stirring. PVA-MA / HPC / HACC / CNF hydrogel was obtained by photocuring, which was recorded as PMHC hydrogel; (4) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the mixed solution C, stirring thoroughly to obtain a mixed solution D, and photocuring to obtain a PVA-MA / HPC / HACC / CNF / I2959 hydrogel, which is denoted as PMHI hydrogel; (5) After the PMHI hydrogel is immersed in sodium citrate solutions of different concentrations, it is immersed in sodium chloride solutions of different concentrations again. After a certain period of time, a high-toughness interpenetrating network hydrogel elastomer is obtained.

2. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The polyvinyl alcohol is type 1799 and has a molecular weight of 200,000 to 205,000.

3. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The molecular weight of the hydroxypropyl cellulose is 100,000 to 500,000.

4. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The chitosan quaternary ammonium salt substitution degree is 95% to 99%; the carboxylated cellulose nanofiber content is 95% to 99.8%, the diameter is 4 to 10 nm, the length is 1 to 3 μm, and the solution pH value is 7 to 8.

5. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The purity of the 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 95% to 99%.

6. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The relative molecular mass of the sodium citrate is 294.10, the concentration of the sodium citrate solution is 0.5 mol / L to 3 mol / L, and the soaking time is 0 to 48 hours.

7. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The concentration of the sodium chloride solution is 1-5 mol / L, and the soaking time is 0-48 hours.

8. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The mixed solution is extruded by pressure at a speed of 5 to 10 mm / s, and then irradiated under a 254 nm to 405 nm ultraviolet lamp for 1 to 30 minutes to form a shape.

9. The method for preparing a 3D printable high-toughness interpenetrating network hydrogel elastomer according to claim 1, characterized in that: The water bath heating temperature is 20-35° C., and the magnetic stirring speed is 30-500 rpm / s.

10. A 3D printable high-toughness interpenetrating network hydrogel elastomer prepared by the preparation method according to claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of photocrosslinked polyvinyl alcohol / nanocrystal cellulose (PVA / CNC) composite film

    CN105820356A

  • Preparation and application of composite gel, polymer scaffold, aggregate and film containing soluble cross-linked chitosan

    CN117835822A

  • Preparation method of composite hydrogel, composite hydrogel and application of composite hydrogel

    CN118221968A